Wasserlandschaften Planen, Bauen und Gestalten mit Wasser (Birkhäuser, 2006)
After decades of being banished from residential areas, water is now becoming an increasingly significant feature in urban design. Whether it is the integration of natural water courses into the built environment, rainwater management, the incorporation of water elements in urban areas for climatic purposes or the creation of oases of tranquility or drama such as pools or fountains - all these aspects are not only encountering renewed interest among architects and urban planners, but they are also greeted with appreciation by the general public. This book reveals the wide variety of possibilities for using water as a creative element in the city, in art, in the landscape and architecture. The works are organized in seven categories and encompass large-scale masterplans, urban plazas and parks, river restorations but also interior design schemes and art objects. Amongst the works documented are the landscape design for Dubai Business Park, a river restoration in Bishan Park in Singapore, landscaping for a new town in Tianjin, China, the schemes for Telecom Park, Taipei and Vuores Central Park in Tampere, Finland, and the design for Civic Square Seattle.Herbert Dreiseitl, born in 1955, is a sculptor, water artist and landscape architect. After his studies, he set up his office, Atelier Dreiseitl, in Überlingen on Lake Constance in 1980. He has realised numerous projects in the fields of stormwater management, water art and landscape architecture. He is active in lecturing worldwide and his work is widely published. Dieter Grau, born in 1963, gardener and landscape architect, has been working for the Atelier Dreiseitl since 1994. In 1996 he became head of the landscape architecture department there. He is involved in planning projects around the world and lectures frequently